Enhanced piezoelectric properties of Pb0.8Ca0.2TiO3 thin films prepared at low temperature by a sol–gel process. Issue 3 (April 2015) - Fu, M.; Zhang, T.Y.; Chen, Y.
Abstract: Highly (100)-orientated Pb0.8 Ca0.2 TiO3 (PCT) thin films were deposited on a Pt/Ti/SiO2 /Si substrate and annealed at 450–600 °C. The effect of the annealing temperature on the orientation and electrical properties of the films was investigated. While all of the PCT thin films were pure crystalline perovskite, the film annealed at 500 °C exhibited higher (100)-orientation, high piezoelectric properties, and lower leakage current. Our results show that low-temperature crystallization of PCT thin films can suppress interfacial diffusion and improve integration with silicon substrate, extending their potential applications in electronic devices such as piezoelectric sensors and piezoelectric transducers.